Handover Nurse Monitoring and Evaluation In Meeting The SNARS Accreditation Standards 1.1 - Yuliastanti, Kurnia; Pohan, Vivi Yosafianti; Hartiti, Tri (University of Muhammadiyah Semarang, 2020)
Sultan Agung Islamic Hospital Semarang as one of the providers of health, education and research services must be supported by a strong organization and good management. The nurse plays an important role regarding the clinical outcome of the client, especially during the handover the process which has an impact on patient safety and the quality of the hospital. The implementation of monitoring and evaluation of handover in this hospital has never been implemented because there are no working tools and regulations that regulate it as a reference for implementation. This study uses the interviews and observations with the approach carried out on 7 - 19 December 2020. Participants consisted of the Responsible Person / Head of the Room, the Responsible Nurse (PPJA) and the Implementing Nurse (PP) in the Baitul Izzah 2 room of the Sultan Agung Islamic Hospital Semarang. This study found 3 themes were found, namely the absence of monitoring and evaluation of handover nurses, lack of understanding of nurses regarding the implementation of handover monitoring and evaluation, the absence of regulations and work tools regarding the handover monitoring and evaluation. Work tools and regulations are very helpful in the implementation of monitoring and evaluation of handover in providing nursing care in the inpatient room. As well as fulfilling SNARS 1.1 Accreditation standards.